2019
DOI: 10.1002/adbi.201900021
|View full text |Cite
|
Sign up to set email alerts
|

FtsZ‐Independent Mechanism of Division Inhibition by the Small Molecule PC190723 in Escherichia coli

Abstract: The small molecule PC190723 was previously identified as an inhibitor of the cell division protein FtsZ in several Gram-positive bacteria. Here, we utilize genetic, chemical, and single-cell approaches to show that PC190723 is also effective in the Gram-negative bacterium Escherichia coli when outer membrane permeability is compromised, and that PC190723 blocks division through a previously unreported FtsZ-independent mechanism of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, no such difference was observed in the absence or presence of PC190723 in cells expressing EcFtsZ ( Fig. 5E and F ) and is consistent with a recent study that concluded that the inhibitory activity of PC190723 on E. coli was independent of FtsZ (Khare et al, 2019). These observations suggested that PC190723 resulted in an early assembly of FtsZ into polymers in the case of SaFtsZ and HpFtsZ, but it did not act on EcFtsZ.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…However, no such difference was observed in the absence or presence of PC190723 in cells expressing EcFtsZ ( Fig. 5E and F ) and is consistent with a recent study that concluded that the inhibitory activity of PC190723 on E. coli was independent of FtsZ (Khare et al, 2019). These observations suggested that PC190723 resulted in an early assembly of FtsZ into polymers in the case of SaFtsZ and HpFtsZ, but it did not act on EcFtsZ.…”
Section: Resultssupporting
confidence: 92%
“…However, PC190723 predominantly affects Gram +ve bacteria and FtsZ from Gram -ve bacteria have been shown or predicted to be resistant (Haydon et al, 2008). Studies in the past on the effects of PC190723 on E. coli have been confusing, with a few reports suggesting an effect on FtsZ polymerization resulting in cell filamentation (Kaul et al, 2014), while others did not find any effect on EcFtsZ (Anderson et al, 2012; Andreu et al, 2010; Khare et al, 2019). The outer membrane has been shown to be a permeability barrier for PC190723 in E. coli (Chai et al, 2020; Khare et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, recently reported derivatives of PC190723 exhibit very low MICs on important Gram-positive pathogens and have low toxicity profiles. Targeting FtsZs in Gram-negative pathogens will be more challenging because of increased barriers to permeability due to the outer membrane, but the small size of many of the compounds reviewed here, along with combination therapy using adjuvants that perturb the outer membrane and/or drug efflux pumps, provide promising future avenues ( Khare et al, 2019 ). Continued development of better small molecule inhibitors that target FtsZ, as well as discovery of small molecules that can inhibit the activity of other conserved bacterial cell division proteins, will require continued collaboration between medicinal chemists, structural biologists and microbiologists.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%